Rustificação de plantas jovens de Coffea arabica L - Novaes, Paula (Universidade Federal de São Carlos, 2007)
Young plants of Coffea arabica grafted over C. canephora were submitted to six watering cycles (WC) during 35 days. Each WC was accomplished until net photosynthesis (PN) close to zero or leaf water potential (Ψ) close to -2.0 MPa in Acauã (AC), Mundo- Novo (MN), and Obatã (OB) cultivars. After 2 WC (about 10 days) gs dropped from 0.15 to 0.01 mol m-2 s-1 in all cultivars changing the pattern of leaf gas exchange in subsequent WC. From 3 to 6 WC the cultivars showed high oscillations of water use efficiency or substomatal CO2 concentration (Ci) besides negative PN at the end of WC. After 3 WC, gs increased faster than PN after watering and Ci increased indicating some damage in photosynthetic machinery. It happened strongly in OB, which showed progressive reduction of PN after 3 WC and the lowest values of Ψ (-2.0 MPa) at the end of 6 WC. The survivorships for cultivars were 80% till 3 WC and 70% after 6 WC. The gas exchange pattern alteration could indicate the potential hardening of AC, MN and OB cultivars. After field plantation of hardened and control (without perivous hardening) Mundo-Novo and Obatã cultivars, with 180-days-old, it was observed significant (p<0.05) greater accumulation of leaf, stem and root biomass in hardened in control plants. Stem diameter, height and the number of leaf and branch were also higher (p<0.05) in previous hardened individuals. Greater differences in crown structure and biomass between control and hardened plants were observed mainly after the first period of low water availability (210 days under field conditions). The higher leaf number and leaf area in more branched crowns could carbon assimilation and grain production. For practical proposes, 3 WC before growing under field conditions are sufficient for changing consistently the leaf gas exchange pattern in 3 cultivars studied, keeping photosynthetic machinery free of damage and high survivorship. Previous hardening proportioned less interrupted vegetative development after transplantation under field conditions in both cultivars.
Keywords: Café - cultivo; Fisiologia vegetal; Rustificação; Estresse hídrico; Biomass; Coffea arabica; Crown structure; Hardening; Growth; Initial development; Leaf area; Net photosynthesis; Stomata conductance; Survivorship; Water use efficiency; CIENCIAS BIOLOGICAS::ECOLOGIA